Topical treatment options for allergic conjunctivitis - Sumari Davis (South African Family Practice)
Allergic conjunctivitis can be classified as an acute or chronic condition. Acute allergic conjunctivitis encompasses seasonal allergic conjunctivitis and perennial allergic conjunctivitis. The more severe chronic conditions include vernal keratoconjunctivitis, acute keratoconjunctivitis and giant papillary conjunctivitis. The mainstay in the treatment of allergic conjunctivitis remains the use of topical dual-acting agents which have mast cell stabilising properties and act as antihistamines. Although corticosteroids are among the most effective agents in the treatment of allergic conjunctivitis, they can cause serious adverse effects and their use should be reserved for short-term “pulse” treatment to gain quick control of the symptoms. Topical nonsteroidal anti-inflammatory drugs can also cause corneal melting. However, their use may be considered in severe cases to reduce the use of topical steroids. Several new agents acting at newly identified targets in the inflammatory process are under investigation for the treatment of allergic conjunctivitis.